No reflow phenomenon in percutaneous coronary interventions in ST-segment elevation myocardial infarction - Gupta, Sanjiv (Indian Heart J, 2016)
Percutaneous coronary intervention (PCI) is effective in opening the infarct related artery and restoring thrombolysis in myocardial infarction flow 3 (TIMI-flow 3) in large majority of ST-elevation myocardial infarction (STEMI). However there remain a small but significant proportion of patients, who continue to manifest diminished myocardial reperfusion despite successful opening of the obstructed epicardial artery. This phenomenon is called no-reflow. Clinically it manifests with recurrence of chest pain and dyspnea and may progress to cardiogenic shock, cardiac arrest, serious arrhythmias and acute heart failure. No reflow is regarded as independent predictor of death or recurrent myocardial infarction. No reflow is a multi-factorial phenomenon. However micro embolization of atherothrombotic debris during PCI remains the principal mechanism responsible for microvascular obstruction. This review summarizes the pathogenesis, diagnostic methods and the results of various recent randomized trials and studies on the prevention and management of no-reflow.